The Influence of Teacher Quality, Teacher Characteristics, and Teaching Experience on School Quality that Impacts Student Performance in Bandung: Evidence from High School - Rospita Siagian; Bhenu Artha (Jurnal Pendidikan West Science, 2023)
This study examines the relationship between teacher quality, teacher characteristics, and teacher teaching experience on school quality and student performance in Bandung using Smart-PLS analysis. The study included 10 middle schools in Bandung, with a total of 150 teachers. The results indicate that teacher quality, teacher characteristics, and teacher teaching experience positively influence school quality, which in turn, impacts student performance. The findings suggest that improving teacher quality and school quality should be a priority for policymakers and school leaders to enhance student outcomes.